Studi kesesuaian kualitas perairan tambak ikan bandeng (Chanos chanos) di Kawasan Ekowisata Mangrove Sungai Tatah - Irawan, Doni; Handayani, Leni (Universitas Sam Ratulangi, 2021)
The research objective was to determine the quality of the milkfish pond waters (Chanos chanos) in the Tatah River Mangrove Ecotourism Area. This research was conducted from March to May 2020. Purposive sampling was one of the research methods used to collect data. Water samples were taken once a week (in the morning, afternoon and evening) from six sampling stations. The parameters observed included the physical and chemical properties of the waters. The data analysis used was scoring. The results of the research on the level of quality suitability of pond waters in the Tatah River Mangrove Ecotourism Area indicated that station 2, and 4 were very suitable level of conformity (S1) meaning that it is potential station while station 1, 3, 5 and 6 were quite appropriate (S2) which means that the areas meet the minimum requirements for use in milkfish (C. chanos) cultivation